Thromboelastography identifies children with rare bleeding disorders and predicts bleeding phenotype. (January 2015) - Zia, A. N.; Chitlur, M.; Rajpurkar, M.; Ozgonenel, B.; Lusher, J.; Callaghan, J. H.; Callaghan, M. U.
Summary Rare bleeding disorders (RBDs) comprise 3–5% of all congenital bleeding disorders. They can evade typical coagulation screening tests and there is a poor correlation between laboratory results and bleeding phenotype. Thromboelastography (TEG) measures coagulation globally in whole blood samples. The aims of this study were to evaluate the utility of TEG as an adjunct to the routine screening tests employed for the diagnosis of RBDs and to correlate TEG results with the bleeding phenotype in RBDs. TEG parameters and clot kinetics were compared to bleeding phenotypes (asymptomatic, mild, moderate and severe) in 26 RBD patients and 30 normal controls. Clot kinetics correlated strongly with RBDs and with the severity of bleeding phenotype with mean maximum rate of thrombus generation (MRTG) 15.4 mm min−1 in controls vs. 6.0 in RBDs (P < 0.0001, Wilcoxin). The mean MRTG was 7.7 in mildly symptomatic, 5.5 in moderately symptomatic and 4.1 in severely symptomatic patients (P < 0.0001, Kruskal–Wallis). Disorders that are often missed by conventional screening tests, dysfibrinogenaemia and platelet disorders displayed a distinctive TEG curve with markedly decreased maximum amplitude (MA) and low MRTG values. Factor XIII and PAI deficient patients displayed increased fibrinolysis in addition to low MRTGs. All patients with RBDs, but none of the normal controls, had abnormal clot kinetics suggesting that TEG may be an effective screening test for RBDs.